Cassava improvement in Africa - Hahn, S.K.; Terry, E.R.; Leuschner, K.; Akobundu, I.; Okali, C.; Lal, R. (1979)
Cassava (Manihot esculenta Crantz) is an important staple food crop in tropical Africa. Production constraints including diseases, insect pests, weeds, soils, cultural practices and socio-economic factors are discussed. Research findings to overcome these constraints are reviewed, with particular emphasis on pest control, varietal improvement and cultural practices. Significant progress has been made in breeding improved clones resistant to cassava mosaic and bacterial blight (Xanthomonas manihotis Starr) with desirable root characteristics, low HCN, resistance to lodging, high yield potential, and of a quality acceptable to the consumers of the region. Sources of resistance to cassava green mite (Mononychellus tanajoa Bondar) have also been identified. Increased benefits from cassava improvement will require growing the improved varieties under good management conditions and at low pest population pressures.